2020
DOI: 10.1021/acs.biochem.0c00257
|View full text |Cite
|
Sign up to set email alerts
|

HD-[HD-GYP] Phosphodiesterases: Activities and Evolutionary Diversification within the HD-GYP Family

Abstract: Cyclic dinucleotides are signaling molecules that modulate many processes, including immune response and virulence factor production. Their cellular levels in bacteria are fine-tuned by metal-dependent phosphodiesterases, namely, the EAL and HD-GYP proteins, with HD-GYPs belonging to the larger HD domain superfamily. In this study, we first focus on the catalytic properties and the range of metal ions and substrates of the HD-[HD-GYP] subfamily, consisting of two HD domains. We identified SO3491 as a homologue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 56 publications
4
25
0
Order By: Relevance
“…Hydrolases are further subdivided into (i) phosphatases, including dGTPases [38], RelA/SpoT [9,17], SAMHD1 [18,19], EF1143 [20,21], etc. and (ii) phosphodiesterases (PDEs), including exoribonucleases [39], PDEases [27][28][29][30][31][32][33][34], Cas proteins [23][24][25][26], and HD-GYPs [14,35,36,40] (Figure 1B). Phosphatases hydrolyze a multitude of (deoxy)nucleotide-based substrates that vary in the identity of their base(s) and the extent of phosphorylation (Figure 2) [3,5,16,22].…”
Section: Characteristics and General Classification Of Hd-domain Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrolases are further subdivided into (i) phosphatases, including dGTPases [38], RelA/SpoT [9,17], SAMHD1 [18,19], EF1143 [20,21], etc. and (ii) phosphodiesterases (PDEs), including exoribonucleases [39], PDEases [27][28][29][30][31][32][33][34], Cas proteins [23][24][25][26], and HD-GYPs [14,35,36,40] (Figure 1B). Phosphatases hydrolyze a multitude of (deoxy)nucleotide-based substrates that vary in the identity of their base(s) and the extent of phosphorylation (Figure 2) [3,5,16,22].…”
Section: Characteristics and General Classification Of Hd-domain Proteinsmentioning
confidence: 99%
“…However, because single amino acid substitutions of each of the GYP domain residues to alanines hardly affect PDE activity [36], its role in catalysis and protein stability remains poorly understood. The GYP motif is considered important for interaction with the GGDEF cyclase (named after its highly conserved Gly-Gly-Asp-Glu-Phe sequence motif) [8] and serves as a substrate specificity element for the recognition of c-di-GMP and its hybrid 3 3 -cGAMP analog [40].…”
Section: Hd-domain Pdes Acting On C-di-gmp and C-gamp; The Hd-gyp Subclassmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the partially conserved Glu residue in the N-terminal loop (E185 in the structure of P. marina PmGH, PDB ID: 4MCW, Figure 1). This acidic residue (Glu or Asp) participates in binding the third metal atom; phylogenetic analyses showed that, depending on the presence or absence of this Glu residue, HD-GYP domains could be split into two families carrying, respectively, trinuclear or binuclear metal centers (45,46,58). For their c-di-GMP phosphodiesterase activity, experimentally studied HD-GYP domains typically require two ferrous (Fe 2+ ) ions, oxidation of either one of them inactivates the enzyme (36).…”
Section: Substrate Binding and Hydrolysis By Hd-gyp Domainsmentioning
confidence: 99%